Swartzia langsdorffii Raddi: morphophysiological traits of a recalcitrant seed dispersed during the dry season - Vaz, Tatiana A. A.; Davide, Antonio C.; Rodrigues-Junior, Ailton G.; Nakamura, Adriana T.; Tonetti, Olivia A. O.; Silva, Edvaldo A. A. da [UNESP] (Cambridge Univ Press, 2016)
Swartzia langsdorffii seeds have recalcitrant characteristics. Nonetheless, dispersal begins in the month with the lowest precipitation in the studied region, which could lead to seed death by desiccation. Therefore, the objectives of this study were: (1) to characterize the physiological behaviour of S. langsdorffii seeds related to their desiccation sensitivity/tolerance; and (2) to assess the morphophysiological characteristics that enable the seeds to remain viable after dispersal. Fruits and seeds were subjected to biometric evaluation and the anatomical and ultrastructural features of the seeds were determined. Field assessments were performed to determine the capacity of the seeds to maintain viability and to verify the relation between seed viability, diaspore water content and environmental variables. Seeds of this species were found to be recalcitrant and showed pores distributed throughout the seed coat, and contained a large number of stomata in the hypocotyl-radicle axis epidermis. Moreover, phenolic compounds were found throughout the radicle region. Seeds remained viable in the soil for up to 7 months after dispersal without a significant decrease in water content, despite the low precipitation and soil water content. Radicle protrusion began 5 months after dispersal and coincided with partial fruit decomposition at the beginning of the rainy season. Thus, the possible microclimate created by the pericarp, with the moisture content of the aril and the soil, the presence of the structures in the axis, such as the pores and stomata, the chemical composition and the morphology of S. langsdorffii seeds could favour maintenance of their viability until the beginning of the rainy season.
Keywords: aril; diaspore; embryonic axis; jacaranda-banana; seed-coat pores; stomata; Swartzia langsdorffii